2002
DOI: 10.1007/s00066-002-0915-x
|View full text |Cite
|
Sign up to set email alerts
|

Virtueller Bolus zur inversen Bestrahlungsplanung bei intensitätsmodulierter Radiotherapie des Mammakarzinoms im Rahmen der adjuvanten Therapie

Abstract: The realization of inverse optimization for IMRT of the breast requires the use of a virtual bolus. Thereby, IMRT in accordance to the consensus recommendations of the EORTC, BCCG and EUSOMA is possible. Especially, the same target definition as in conventional technique may be used. IMRT techniques with a conventional beam arrangement of two tangential fields or multiple beam techniques can be realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In situations where the PTV extends up to or near the surface of the patient, the treatment planning system compensates by boosting beamlets tangential to the superficial region. When the patient is displaced from their planned position, notable regions of high dose are presented upon a small movement in the patient's position, even when the original plan shows good homogeneity 1 , 2 , 3 . Such an effect is distinct from other potential sources of increased superficial dose, such as the bolus effect of immobilization masks (4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situations where the PTV extends up to or near the surface of the patient, the treatment planning system compensates by boosting beamlets tangential to the superficial region. When the patient is displaced from their planned position, notable regions of high dose are presented upon a small movement in the patient's position, even when the original plan shows good homogeneity 1 , 2 , 3 . Such an effect is distinct from other potential sources of increased superficial dose, such as the bolus effect of immobilization masks (4) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies 1 , 2 have suggested the use of a “pretend bolus” (PB), applied in treatment planning but not during the actual treatment, as a method to reduce surface dose and high‐dose regions. This method leads the planning system into believing that the optimized PTV is at a depth within the patient rather than at the skin surface, giving adequate buildup of material to account for the skin sparing effect.…”
Section: Introductionmentioning
confidence: 99%
“…Various tricks are used by treatment planners to avoid these problems. One method is the use of 'pretend bolus' as proposed by Thilmann et al (2002). This involves the adding of bolus in the planning process, which is not used for treatment.…”
Section: Introductionmentioning
confidence: 99%